1971
DOI: 10.1073/pnas.68.4.740
|View full text |Cite
|
Sign up to set email alerts
|

Inducers of Interferon Inhibit the Mitotic Response of Liver Cells to Partial Hepatectomy

Abstract: Partially hepatectomized mice were injected with inducers of interferon, and the mitotic activity of liver cells was measured. The inducers were polyriboinosinic * polyribocytidylic acid, poly(I * C), Newcastle disease virus, and statolon. Each inhibited the mitosis of liver cells. Poly(I-C) was effective in doses as low as 1 ug per mouse. Polyriboinosinic acid, poly(I), had no inhibitory effect. These results extend the spectrum of action of inducers of interferon to inhibition of mitotic division of an aneop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1973
1973
1981
1981

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Poly(I C) may generally enhance the immunological ability of the host and exclude antigenically different tumor cells. Recent evidence shows that poly(I * C) inhibits isoproterenol-stimulated DNA synthesis in the mouse salivary gland (12), phytohemagglutinin-stimulated DNA synthesis in lymphocyte incubations (14), and rat liver cell mitosis induced by partial hepatectomy (13). Furthermore, our study shows that the double-stranded synthetic RNA inhibited synchronized HeLa cell DNA synthesis.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Poly(I C) may generally enhance the immunological ability of the host and exclude antigenically different tumor cells. Recent evidence shows that poly(I * C) inhibits isoproterenol-stimulated DNA synthesis in the mouse salivary gland (12), phytohemagglutinin-stimulated DNA synthesis in lymphocyte incubations (14), and rat liver cell mitosis induced by partial hepatectomy (13). Furthermore, our study shows that the double-stranded synthetic RNA inhibited synchronized HeLa cell DNA synthesis.…”
Section: Discussionmentioning
confidence: 52%
“…Poly(I C) blocks carcinogenesis by dimethylbenzanthracene (11). In addition it inhibits isoproterenol-stimulated DNA synthesis in salivary glands of mice (12), rat liver cell divisions stimulated by partial hepatectomy (13). Poly(A * U) depresses phytohemagglutinin-induced DNA synthesis in lymphocyte culture (14).…”
mentioning
confidence: 99%
“…In this respect, it is important to note that the mitogenic action of poly I *poly C in fibroblasts (our study) is in marked contrast to the observations that poly I *poly C is both a potent inhibitor of tumor growth (Mohr et al, 1972) and an inhibitor of DNA synthesis in synchronized HeLacells (Teng et al, 1973), isoproterenol-stimulated salivary glands (Serota and Raserga, 1970). and regenerating liver cells (Jahiel et al, 1971).…”
Section: Dna Synthesismentioning
confidence: 99%
“…Inoculation of hamsters with poly(rI).poly(rC) resulted in the discovery of a hemopoetic cell-colony formation inhibitor in the serum of these animals by McNeill and his colleagues (McNeill and Fleming, 1971;Fleming et al, 1972;McNeill et al, 1972). Interferon inducers [poly(rI).poly(rC), Newcastle disease virus and statolon] were reported to inhibit the mitotic response of liver cells to partial hepatectomy (Jahiel et al, 1971); later interferon itself was shown to have the same effect (Frayssinet et al, 1973).…”
Section: Cell Effects In Vivomentioning
confidence: 99%